2020
DOI: 10.1155/2020/5364521
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal and Postpartum Depression: Prevalence and Associated Risk Factors among Adolescents’ in KwaZulu-Natal, South Africa

Abstract: Background. Maternal depression is a major public health concern as it affects both mothers and their children. Antenatal depression, which is often underdiagnosed, has been associated with preterm labour, low birth weight, and intrauterine growth restriction. Research has demonstrated that postpartum depression is associated with mother-infant bonding impairment, child abuse, child neglect, maternal substance abuse, and self-harm. Globally, the prevalence of depression in pregnant and postpartum adolescents v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 67 publications
11
49
1
1
Order By: Relevance
“…In this study, social support was associated with antenatal depression; similar findings were reported from the study done in the USA [ 54 ], KwaZulu-Natal, South Africa [ 35 ], and Kenya [ 44 ]; a systematic review and meta-analysis conducted in Ethiopia [ 22 ]; and another systematic review in Ethiopia [ 8 ] and Hawassa, Ethiopia [ 39 ]. This might be explained by social support that has been shown to promote mental health and acts as a buffer against depression [ 55 ], so lack of social support could be implicated for the high risk of depression during pregnancy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, social support was associated with antenatal depression; similar findings were reported from the study done in the USA [ 54 ], KwaZulu-Natal, South Africa [ 35 ], and Kenya [ 44 ]; a systematic review and meta-analysis conducted in Ethiopia [ 22 ]; and another systematic review in Ethiopia [ 8 ] and Hawassa, Ethiopia [ 39 ]. This might be explained by social support that has been shown to promote mental health and acts as a buffer against depression [ 55 ], so lack of social support could be implicated for the high risk of depression during pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…On the contrary, the finding of this study is higher than 9.18% and 12.3% in the study done in Mumbai and Bengaluru, India, respectively [ 32 , 33 ], and 14.2% in Rio de Janeiro, Brazil [ 34 ]; this may be because a better health service provision of the countries compared to Ethiopia. The finding of this study is almost similar to 15.9% in Southern KwaZulu-Natal, South Africa [ 35 ], 17.9% in the Dubti Hospital Afar region [ 21 ], and 15.2% in Aneded woreda, Amhara Region, Ethiopia [ 36 ]. But the result is lower than 24.3% in a systematic review and meta-analysis in South Asia [ 37 ], 24.5% in Abeokuta North Local Government Area in Nigeria [ 38 ], 21.5% in the findings from, 21.28% in a systematic review and meta-analysis in Ethiopia [ 22 ], and 23.5% in another systematic review and meta-analysis in Ethiopia [ 8 ], Hawassa [ 39 ], and 24.9% in Addis Ababa [ 40 ].…”
Section: Discussionsupporting
confidence: 81%
“…Another study conducted in Addis Ababa, Ethiopia by Biratu et al on antenatal depression in pregnant women using EPDS scale (n=393), found prevalence of antenatal depression to be 24.94%(95% CI: 20.85-29.30%) (13). In another Ethiopian study conducted by Dibaba et al pregnant women (n=627); the prevalence of depressive symptoms during pregnancy on EPDS scale was 19.9% (95% CI: 16.8-23.1%) (14) and Govender et al in South Africa found (n=326) the prevalence of depression among the pregnant participants was found to be 15.9% using EPDS (15).…”
Section: Studies On Local Burden Associated With Adolescent Peripartumentioning
confidence: 90%
“…Scoring is by summation of the boxes on PHQ-9 questionnaire (For every Not at all = 0; Several days = 1; More than half the days = 2; Nearly every day = 3). Interpretation of Total Score: Depression Severity 1) Minimal depression (1-4), 2) Mild depression (5)(6)(7)(8)(9), 3) Moderate depression (10)(11)(12)(13)(14), 4) Moderately severe depression (15)(16)(17)(18)(19), 5) Severe depression (20)(21)(22)(23)(24)(25)(26)(27). It too has been used widely to screen for depressive symptoms globally and widely validated in different patient populations in SSA.…”
Section: The Edinburgh Postpartum Depression Scale (Epds)mentioning
confidence: 99%
“…Research evidence reveals that the stresses of life, especially around pregnancy and childbirth, can affect the emotions of women and behavior of many mothers, hence increasing the risk of depression during pregnancy and after childbirth 14 . Socio-determinants, i.e.…”
Section: Introductionmentioning
confidence: 99%